2019
DOI: 10.1097/ypg.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Clinical association to FKBP5 rs1360780 in patients with depression

Abstract: The FKBP5 protein is of importance for the function of the glucocorticoid receptor. The purpose of the present study was to examine the possible association between the different genotypes of rs1360780 in the FKBP5 gene, and clinical symptoms in patients with unipolar depression. Seven hundred eighteen patients and 673 controls from the Danish Psychiatric Biobank were participated. No association was found between any genotype and diagnosis of unipolar depression. It was found that the group of depressed patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A number of genetic-related factors, genomic regions, polymorphisms, and other related aspects have been examined with respect to depression [ 61 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ,...…”
Section: Resultsmentioning
confidence: 99%
“…A number of genetic-related factors, genomic regions, polymorphisms, and other related aspects have been examined with respect to depression [ 61 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ,...…”
Section: Resultsmentioning
confidence: 99%
“…FKBP5 has further been suggested to have a dual effect with positive environment. For example, appraisal among psychiatric patients (Cristóbal-Narváez et al 2020 ) has shown an increase in positive responses to the treatment of psychiatric illness and depression (Binder et al 2004 ; Dam et al 2019 ), while other studies have shown contrary findings (Isaksson et al 2016 ; Pérez-Pérez et al 2018 ). Previous knowledge regarding the associations of parenting style, ELS and the FKBP5 gene on depression provides a cogent rationale for evaluating cG × E interaction effects.…”
Section: Introductionmentioning
confidence: 99%